Biological, dielectric and nonlinear optical properties of chelated bimetallic 1-D coordination polymer - M.R. Sabitha Mohan; Rani Pavithran; I. Hubert Joe; P. Aswathy (Results in Chemistry)
Single crystals of bimetallic 1-D coordination polymer, NiZnEDTA were grown by the single gel diffusion method. The agar-well diffusion technique and MTT assay test were done to examine the antimicrobial and anticancer activity of NiZnEDTA. The test outcomes of the MTT assay give a preliminary indication of the anticancer potential of the sample on MDA-MB-231 cells and its nontoxic nature to normal L929 cells. The third-order nonlinear optical characterization of NiZnEDTA was studied by Z-scan technique.